O crucifixo nos tribunais: a neutralidade religiosa e o uso dos espaços públicos - Pantaleão Filho, Cleanto Alves (2016)
This thesis aims to analyze the cross exhibition in sessions halls and audiences of the judiciary, considered the religious freedom and the limitations arising from the idea of State neutrality. It is known that the 1988 Constitution protects freedom of expression of thought, conscience and religion, in its various aspects, proclaiming, on the other hand, the neutrality of the state, to reinforce these same freedoms. Thus, the aim is to avoid confusion between state and religion, admitted, however, collaboration of public interest, in respect of attitude to the beliefs and individual choices of citizens. In modern societies, the dualism between the civil power and religion has to do with laicity and a broader phenomenon that took the name of secularism, meaning the loss of space of religion in societies or even decreased idea religious belonging. It is based on this finding that the work develops with reference to concepts such as civil society and rule of law relevant to an accurate understanding of the problem. The methodology consists of bibliographic and documentary research through books and thesis, in addition to the legislation and some precedents related to the topic in question, looking to investigate whether, even though the predominantly Catholic Brazilian people and recognized the strong influence that Christian values exercise on the public authorities, it is possible to sustain the symbolic differentiation state, a republic that is said secular and democratic and which has as one of the fundamental objectives to promote the good of all, without any form of discrimination. Starting from the idea that the presence in buildings and public institutions, symbols and Catholic imagery, like the crucifix, has some difficulty in reconciling the guarantee of religious freedom and the principle of laicity, the idea is to exactly propose a solution who can respect pluralism and diversity in a context where Catholicism remains a strong presence.